Acoustic Emissions in Geotechnical Engineering Practice 1981
DOI: 10.1520/stp28343s
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Behavior and Monitoring of Soils

Abstract: As far as nondestructive testing methods are concerned, acoustic emission techniques are relatively recent additions to the rock monitoring area (dating from the late 1930's) and to the metal testing area (dating from the 1950's). Its application to soils is an even more recent event with little activity prior to the 1970's. However, over the past five to ten years, interest has been generated in the soils area to the point where at least five equipment manufacturers are currently marketing acoustic emission s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 8 publications
6
54
0
1
Order By: Relevance
“…This observation is consistent with 5 laboratory experiments (e.g. Koerner et al 1981). The normalized difference (%) between the maximum amplitude of the signal and the median value of all maximum amplitudes for the considered event also show drastic attenuation with distance (Fig.…”
Section: Waveform Attenuation Pattern To Estimate Source Proximitysupporting
confidence: 91%
“…This observation is consistent with 5 laboratory experiments (e.g. Koerner et al 1981). The normalized difference (%) between the maximum amplitude of the signal and the median value of all maximum amplitudes for the considered event also show drastic attenuation with distance (Fig.…”
Section: Waveform Attenuation Pattern To Estimate Source Proximitysupporting
confidence: 91%
“…The most significant contribution in the area of AE behaviour of soil has been made by Koerner et al (1981) who carried out extensive laboratory and field studies of both fundamental AE characteristics of soil and field applications. This work demonstrated that deforming soil produces detectable AE and that the levels of emissions are directly related to the stress state of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…inter-particle friction). Koerner et al (1981) and Dixon et al (2003) found that AE generated by soil is influenced by particle size and shape, with larger more angular particles generating greater amplitude stress waves as a greater magnitude of work is required to overcome interlock. Other properties that influence the AE response of soil include; grading, moisture content and plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Koerner et al, 1981), and they form a significant percentage of buried pipelines. This study therefore focused on steel pipes.…”
Section: Introductionmentioning
confidence: 99%
“…Generated AE rates are proportional to applied displacement rates, where the coefficient of proportionality Smith et al Monitoring Buried Pipe Deformation Using AE: Quantification of Attenuation 17/08/2016 3 is dependent on the depth to the shear surface and the distance AE propagates along the waveguide to the ground surface where it is measured. Quantifying this magnitude of attenuation for each installation is essential to deriving slope displacement rates from measured AE rates, which can be used to warn users of accelerating slope deformation behaviour to enable evacuation of vulnerable people and timely repair and maintenance of critical infrastructure (Koerner et al, 1981;Nakajima et al, 1991;Smith et al, 2014a;Smith et al, 2014b;Dixon et al, 2015a;Dixon et al, 2015b;Smith, 2015;Smith & Dixon, 2015;Smith et al, 2016).[Insert Figure 1 here] Developments in AE monitoring of pipe networks (e.g. Alleyne & Cawley, 1992;Alleyne & Cawley, 1997) for the detection and location of defects (e.g.…”
mentioning
confidence: 99%